Ḍakṭara Muhammada Enāmula Haka - Majira Uddīna, Muhammada, 1939- (Ḍakṭara Muhammada Enāmula Haka Smrti Parishada, 1984)
Biography of Muhammad Enamul Haq, 1906-1982, Bengali litterateur and linguist from Bangladesh.